Is there a pace-of-life syndrome linking boldness and metabolic capacity for locomotion in bluegill sunfish? - Binder, Thomas R.; Wilson, Alexander D.M.; Wilson, Samantha M.; Suski, Cory D.; Godin, Jean-Guy J.; Cooke, Steven J. (Animal behaviour, 2016)
The concept of behavioural syndromes (i.e. correlations between behavioural traits) has provided an important framework for understanding individual variation in animal behaviour and its link to individual variation in physiology and life-history traits. The pace-of-life syndrome concept posits that behavioural, physiological and life-history traits coevolve in response to correlated selection pressures, and therefore predicts a positive correlation between boldness (i.e. exploration and risk taking) and metabolic capacity for locomotor performance in individuals. We tested for a pace-of-life syndrome linking boldness and metabolic capacity for locomotor activity in juvenile bluegill sunfish, Lepomis macrochirus. Individual fish were screened and classified as bold or shy using an established refuge emergence test. Subsequently, the aerobic and anaerobic metabolisms of bold and shy individuals were quantified using respirometry and by measuring the metabolic by-products of white muscle anaerobic glycolysis following exhaustive exercise, respectively. Bold fish demonstrated 25% greater metabolic scope for activity (i.e. aerobic capacity) than shy fish, which was attributable to a 15% greater maximum metabolic rate. However, there was no significant difference in resting metabolic rate or anaerobic energy expenditure (i.e. anaerobic capacity) between bold and shy fish. These results partially support a pace-of-life syndrome linking boldness and aerobic metabolism in juvenile bluegill sunfish, but did not reveal a link between boldness and anaerobic metabolism. Our findings suggest that aerobic and anaerobic capacities may be subject to different selection pressures, and that physiological processes governing maximum anaerobic performance in fishes are independent from behavioural and physiological traits related to boldness. •We quantified aerobic and anaerobic metabolisms of bold and shy bluegill sunfish.•Bold fish had greater maximum metabolic rates and metabolic scopes for activity.•Bold and shy fish did not differ in resting metabolic rate or anaerobic metabolism.•Results support a pace-of-life syndrome linking boldness and aerobic capacity.